PHASE MORPHOLOGY OF NR, BR, AND EPDM BLENDS PRODUCED BY AN OPTIMIZED SEQUENTIAL MIXING PROCEDURE - Gogelein, C.; Hough, P. (Rubber Chemistry and Technology, 96(3): 2023. 307-336., 2023)
The use of EPDM in NR/BR blends for imparting ozone resistance is well known, as are the challenges of retaining desired mechanical properties in the cured rubber due to uneven distributions of carbon black and cure system across the blended polymer phases, favoring the NR/BR phase. This work explores how different sequential mixing options and mixing intensity can affect polymer phase dispersion and filler distribution, showing that excellent cured physical properties can be obtained using a commercially viable sequential mixing process where a proportion of the filler, cure system, and other compounding ingredients is first mixed into an EPDM masterbatch compound, which is subsequently used in a second mixing stage when it is combined with NR/BR at a suitable level to achieve good ozone resistance. Because only a proportion of the EPDM masterbatch is added to the second mixing stage, further filler, cure system, and other compounding ingredients are also added to reach the desired levels of the final compound. Variations of the sequential mixing process are reported, including the addition of a small amount of BR to the EPDM masterbatch and the use of an extended milling process. This study confirms that sequential mixing allows the retention of carbon black within the dispersed EPDM phase and shows how the EPDM masterbatch composition and the intensity of mixing can influence the phase morphology of EPDM/NR/BR blends. For comparison, an NR/BR control compound, typical of that used in tire sidewalls, is included in the evaluation. By applying transmission electron microscopy and atomic force microscopy imaging, phase domain sizes are evaluated quantitatively, and the Young$1 (Bs moduli of the rubber phases are determined. The phase morphology is rationalized by the Hansen solubility parameters and the volume fractions of the rubber phases.s
Keywords: EPDM blends